HYPERTENSION PREVALENCE AND LIFE STYLE IN SEMI RURAL URBAN WITH WHO INSTRUMENT ANALYSIS - Augie, Dwichy; Hardja, Bebby Alfiera Riyandina; Jariah, Ainun; Ismah, Zata (LIFE: International Journal of Health and Life-Sciences, 2020)
Non-communicable diseases, also known as chronic diseases, tend to last longer and are the result of a genetic combination, physiological, environmental and behavioral factors. Non-communicable diseases kill 41 million people each year, equivalent to 71% of all deaths globally. People of all age groups, region and countries are at risk of contracting non-communicable diseases. (WHO, 2018) The research method used in this study is a quantitative descriptive research method with a cross-sectional design. The population of this study is the population of semi-rural urban areas, Lubuk Pakam, Deli Serdang Regency. The sample consisted of 120 people; sampling method used the accidental sampling method with stepwise WHO instrument. Distribution majority respondent more have normal blood pressure with a percentage of 68.33%, pre-hypertension (22.5%), and hypertension amounted to 9.167% with many factors.